Research of wood waste concentration influence on composite fuel energy characteristics based on low-grade 2b coal from "Borodinskoe" deposit; MATEC Web of Conferences; Vol. 92 : Thermophysical Basis of Energy Technologies (TBET-2016) - Yankovsky S. A. Stanislav Aleksandrovich; Matveev A. S. Aleksandr Sergeevich; Tolokolnikov A. A. Anton Andreevich; Zenkov A. V. Andrey Viktorovich (2017, 2017)
Title screen